Promotion of Purbalingga Tourism Object Using Augmented Reality Location Based Service & Virtual Reality 360° Based on Android - Gema Kharismajati; Rusydi Umar; Sunardi Sunardi (JUITA : Jurnal Informatika, 2021)
One of the technologies that can be used as an attraction in Purbalingga Regency is Augmented Reality (AR) merging virtual objects with real objects, where those objects can be seen in real-time. And using the Location-Based Service (LBS) method, this method is a service with the main parameters being the position and location of the user. LBS Location Based Service will be enhanced with Google Maps and GPS (Global Positioning System) to find its user position and information about several locations to be visited. Virtual Reality (VR) brings users can interact in a virtual world environment simulated by a computer, so that users feel they are inside. The appearance of the Image object using 3600 panoramic so that it can display images indefinitely and not cut and can look around the image. Application creation is done by Multimedia Development Life Cycle (MDLC) and Unity3D. The application has been successfully operated on the Android operating system with minimum specifications of 2GB RAM and KitKat version 4.4 OS. The results of the study have been conducted through a questionnaire to 15 respondents with 15 questions earned an The total value of the frequency of each question gets a score of 1,009 or a percentage of eligibility of 89,68% starting that the application is well worth using. Based on the black-box test, the application has been running properly and can display Location Based Service and 3600 panoramic and its information.